Environmental & architectural phenomenology. Vol. 1, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1990)
Vol. 1, No. 3, Fall 1990 (includes "citations received,” book review of Thomas Thiis-Evensen's Archetypes in Architecture, and essay by Anne Vittoria).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals